2018
DOI: 10.1073/pnas.1720140115
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based discovery of glycomimetic FmlH ligands as inhibitors of bacterial adhesion during urinary tract infection

Abstract: SignificanceThe emergence of multidrug-resistant bacteria, including uropathogenic Escherichia coli (UPEC), makes the development of targeted antivirulence therapeutics a critical focus of research. During urinary tract infections (UTIs), UPEC uses chaperone–usher pathway pili tipped with an array of adhesins that recognize distinct receptors with sterochemical specificity to facilitate persistence in various tissues and habitats. We used an interdisciplinary approach driven by structural biology and synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
77
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 59 publications
6
77
0
1
Order By: Relevance
“…Therefore, FimH antagonists, such as d-mannose, have gained increasing consideration and proven to be effective for the treatment and/or prevention of acute and recurrent UPEC-mediated UTIs [21,22,[24][25][26][27]. Furthermore, d-mannose represents a real alternative to antibiotic regimens, reducing the burden of antibiotic resistance and associated side effects [2,14,31,[34][35][36]. Our results show that d-mannose affected neither bacterial viability, shape, or motility nor interfered with the activity of the tested antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, FimH antagonists, such as d-mannose, have gained increasing consideration and proven to be effective for the treatment and/or prevention of acute and recurrent UPEC-mediated UTIs [21,22,[24][25][26][27]. Furthermore, d-mannose represents a real alternative to antibiotic regimens, reducing the burden of antibiotic resistance and associated side effects [2,14,31,[34][35][36]. Our results show that d-mannose affected neither bacterial viability, shape, or motility nor interfered with the activity of the tested antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are among the most common infectious diseases, affecting more than 150 million people worldwide each year [1,2]. Clinically, UTIs are distinguished into cystitis or lower UTI, affecting the bladder, and pyelonephritis or upper UTI, involving the kidneys [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, grampositive bacteria comes in the second degree, for example, S. saprophyticus is the second most common cause UTI in females with percentage between 30% to 40% [23]. Most gram-negative bacteria as well as some of gram-positive bacteria have different virulence factors such as fimbriae, biofilms and capsule that enabling these pathogens to attachment, persistence and colonization in the bladder epithelium of urinary tract and cause infection [24,25]. Our findings showed that most bacterial isolates were resistant to most antibiotics with high percentages as shown in Table 2 and Figure 1, these results are similar with many previous studies in different countries such as, in Egypt, Uganda, India and Nigeria [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-associated-UTIs are common in more than 80% of all ICU patients with indwelling catheter (more than 1 million such cases found in US) and should be avoided unless there is medically necessity [46][47][48]. Dietary habits seem to be an important risk factor for UTI recurrence dietary guidance could be a first step toward prevention [42,43,[46][47][48][49][50][51][52][53][54][55][56][57]. After anemia, UTIs are the second common complications in pregnant women [58].…”
mentioning
confidence: 99%